(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Integrating MANETs (Mobile Ad-hoc Networks) nodes to the Internet require either a connection to the Internet or they can connect to the Internet through the Internet gateways. For the second case if a node in a MANET has discover the gateway to connect to the fixed hosts in the Internet and it can be done either by broadcasting a gateway discovery request message initiated by nodes itself or by broadcasting periodic gateway advertisement messages from the gateways. End to end packet delay and throughput are strongly dependent on the time needed to discover the gateways.Nodes in a MANET use number of hops as metric to select a path to a gateway, if all the nodes select its nearest gateway to access the Internet then there may be situations when the network performance degrades because some nodes along the path have too many packets waiting in the queue. This paper presents a novel solution to access internet through mobile nodes in ad hoc network. Here the gateway replies with an advertisement message which is broadcasted to the whole network instead of sending a unicast reply to the requesting node. The traffic load taken into account along a path in addition with minimum hop count to select an efficient gateway. The AODV routing protocol has been used for routing in the MANET domain. A new strategy of gateway discovery was investigated and impact of new metric on the gateway selection in NS-2 was observed. Simulation results show that the proposed scheme outperforms over the existing scheme with high throughput and lower end to end delay.